The highly qualified teacher : what is teacher quality and how do we measure it? - Strong, Michael, 1945- (New York : Teachers College Press, 2011)
Provides an accessible overview of the research related to teacher quality, and introduces a new method for evaluating teachers based on extensive fieldwork in schools. --from publisher description
Includes bibliographical references (p. 123-142) and index.
Keywords: Educational accountability -- United States; Teacher effectiveness -- United States; Academic achievement -- United States